(untitled) (Revista LIDER, 2014)
The Menonita movement has been characterized by its mobility and resilience. This study investigates the causes that explain the above, with support of literature on the subject and primary sources. It concludes that this minority has been able to preserve its character in relation to its confession, ideology and modus vivendi.